2022
DOI: 10.1186/s12917-022-03554-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary plasticity of zoonotic porcine Deltacoronavirus (PDCoV): genetic characteristics and geographic distribution

Abstract: The emergence and rapid spread of the acute respiratory syndrome coronavirus-2 have confirmed that animal coronaviruses represent a potential zoonotic source. Porcine deltacoronavirus is a worldwide evolving enteropathogen of swine, detected first in Hong Kong, China, before its global identification. Following the recent detection of PDCoV in humans, we attempted in this report to re-examine the status of PDCoV phylogenetic classification and evolutionary characteristics. A dataset of 166 complete PDCoV genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…A typical pattern of genetic evolution in coronaviruses is the occurrence of interspecies recombination [41]. Recombinants between different PDCoV strains have been reported in previous reports [31,42,43]. Therefore, the recombination events of all the S gene sequences from Guangxi province were analyzed in this study, and two strains with recombination signals were found.…”
Section: Discussionmentioning
confidence: 85%
“…A typical pattern of genetic evolution in coronaviruses is the occurrence of interspecies recombination [41]. Recombinants between different PDCoV strains have been reported in previous reports [31,42,43]. Therefore, the recombination events of all the S gene sequences from Guangxi province were analyzed in this study, and two strains with recombination signals were found.…”
Section: Discussionmentioning
confidence: 85%